A Low‐Strain Potassium‐Rich Prussian Blue Analogue Cathode for High Power Potassium‐Ion Batteries. (5th May 2021) - Li, Lin; Hu, Zhe; Lu, Yong; Wang, Chenchen; Zhang, Qiu; Zhao, Shuo; Peng, Jian; Zhang, Kai; Chou, Shu‐Lei; Chen, Jun
Abstract: Most of the cathode materials for potassium ion batteries (PIBs) suffer from poor structural stability due to the large ionic radius of K +, resulting in poor cycling stability. Here we report a low‐strain potassium‐rich K1.84 Ni[Fe(CN)6 ]0.88 ⋅0.49 H2 O (KNiHCF) as a cathode material for PIBs. The as‐prepared KNiHCF cathode can deliver reversible discharge capacity of 62.8 mAh g −1 at 100 mA g −1, with a high discharge voltage of 3.82 V. It can also achieve a superior rate performance of 45.8 mAh g −1 at 5000 mA g −1, with a capacity retention of 88.6 % after 100 cycles. The superior performance of KNiHCF cathode results from low‐strain de‐/intercalation mechanism, intrinsic semiconductor property and low potassium diffusion energy barrier. The high power density and long‐term stability of KNiHCF//graphite full cell confirmed the feasibility of K‐rich KNiHCF cathode in PIBs. This work provides guidance to develop Prussian blue analogues as cathode materials for PIBs. Abstract : A low‐strain potassium‐rich K1.84 Ni[Fe(CN)6 ]0.88 ⋅0.49 H2 O (KNiHCF) was prepared by a facile co‐precipitation method. The KNiHCF//graphite full cell exhibits high rate performance, superior cycling stability, and high power density. This work would offer an insight into design of the low‐strain cathode materials for PIBs.